The Effect Of Black Tea Consumption On Teeth Coloring In The Community - Mayangsari, Nino; Chasanah, Niswatun; Nurmalasari, Afrida; Usviany, Veny; Alfah, Sitti; Mainassy, Meilisa Carlen; Sipahutar, Pongki (International Journal of Health Sciences, 2024)
Tea is a type of plant that is popular as a drink. In general, based on the processing method, tea can be classified into three types, namely green tea, olong tea and black tea. The aim of this research is to find out whether there is an effect of tooth coloring on people who consume black tea. The method used is literature study to find theoretical references that are relevant to the cases or problems found. The data used comes from journals, scientific literature, rivew, which contains tooth coloring sheets in people who consume black tea. The results of the research show that there is a relationship between public knowledge and tooth coloring. The conclusion is that the effect of tooth coloring on people who consume black tea is due to the lack of public knowledge about the content of black tea which contains a lot of tannins, which can cause teeth to change color from brown to black.